Tumours of Oddi: Diagnosis and Surgical Treatment. Issue 2 (1992) - Nordlinger, B.; Jeppsson, B.; El-Khoury, W.; Hannoun, L.; Frileux, P.; Huguet, C.; Malafosse, M.; Parc, R.
Abstract : A retrospective review of 56 patients operated upon for tumours of Oddi was performed in order to determine optimal diagnostic and therapeutic procedures. Common presenting symptoms were jaundice (86%) and anemia (21%). Mean size of the tumour was 2.3 cm. Five tumours were benign and 51 were malignant. According to the classification of Martin, five were grade I: 10 grade II; 18 grade III; and 18 grade IV. Forty-seven patients underwent resection of the tumour: three local excisions for small benign tumors, six ampullectomies (followed in three by a Whipples' procedure for recurrence) and 41 Whipples' procedures. The hospital mortality was 5.3%, minor complications appeared in 21%. The overall five years survival was 41%. It was 75% in grade I, 50% in grade II, 40% in grade III and 10% in grade IV. The patients who received ampullectomies were alive with a follow-up of one, two and three years. All patients operated upon for a benign tumour were alive except one who died of cardiac failure. Ultrasonography and duodenoscopy are the most useful tests for the diagnosis of tumours of Oddi. Prognosis depends on the degree of infiltration of the duodenal wall and the presence of positive lymph nodes. Whipples' procedure is best but ampullectomy can be used in elderly or poor risk patients. Malignant tumours of the ampullary region are infrequent and reported to constitute betwee 0.02 and five percent of all cancers of the digestive tract. With wider application of endoscopic techniques, there has been an increasing interest in this group of tumours during recent years. In the literature tumours of Oddi are usually reported in the group of periampullary tumours, including tumours of the ampulla itself, duodenal wall surrounding the ampulla, the distal part of the common bile duct and head of the pancreas. We have wanted to distinguish specifically the tumours of the ampulla of Vater and have adopted the term tumour of Oddi introduced by Marchal and Hureau.The sphincter of Oddi exactly delineates the junction between the bile duct, pancreatic duct and duodenum. We wanted to avoid using the anatomic term ampulla of Vater, since this structure rarely appears as an ampulla. This then excludes tumours in the head of pancreas, common bile duct above ths phincter of Oddi and tumours of the duodenal wall adjacent to the papilla. These tumours seem to behave differently from other pancreatic tumours, as they carry a different prognosis and need special attention. We have therefore reviewed retrospectively 56 patients with tumours of Oddi with special reference to diagnosis, histopathologic examination and surgical therapy.